Global burden of motor neuron diseases: mind the gaps - Hardiman, Orla (My University, 2018)
According to the International Classification of Diseases ninth (ICD-9) and tenth (ICD-10) editions, the category of motor neuron diseases comprises amyotrophic lateral sclerosis, progressive muscular atrophy, primary lateral sclerosis, progressive bulbar palsy, spinal muscular atrophy, and hereditary spastic paraparesis. Spinal muscular atrophy and hereditary spastic paraparesis have a genetic basis, whereas amyotrophic lateral sclerosis, progressive bulbar disease, and primary lateral sclerosis, all of which are adult forms of motor neuron disease, have both familial and sporadic forms. Spinal muscular atrophy is a disease of infancy and childhood, hereditary spastic paraparesis often presents in childhood, and the remaining forms of motor neuron disease occur mostly in people aged older than 50 years. All motor neuron diseases are rare (rare diseases are defined by a prevalence of <1 per 2000 population in Europe),1 and obtaining sufficient data to generate a global burden for all motor neuron diseases is challenging. By systematic analysis of all available data between 1990 and 2016, from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2016 now reported in The Lancet Neurology, the GBD 2016 Motor Neuron Disease Collaborators have provided the first report of the burden of motor neuron diseases for 195 countries and territories.
Keywords: Motor neuron diseases; Amyotrophic lateral sclerosis (ALS)